Guidance and Counseling Strategy in Improving Student Learning Discipline at MTSN 1 Cirebon City - Seviola Nabila Fantona; Nur Lutfi Sakinah; Nani Nasiroh; Nafisah Djabutafuan; Vany Dwi Putri (Interpersonal: Jurnal Bimbingan Konseling Islam, 2026)
Learning discipline is one of the key determinants of student success in the learning process. This study aims to describe the guidance and counseling (BK) strategies implemented at MTsN 1 Cirebon City to improve the learning discipline of eighth-grade students, with a focus on educative sanctions based on religious values, mandatory classroom cleaning duties before school dismissal, and the relationship between religious understanding and the formation of disciplined behavior. A descriptive qualitative method was employed, with data collected through in-depth interviews with three BK teachers, each representing grade levels VII, VIII, and IX respectively. Data were analyzed using the Miles and Huberman model. The results reveal that the eighth-grade BK teacher applies a holistic approach integrating Islamic values into every strategy, including sanctions in the form of reading and writing Qur'anic surahs, cleaning the school environment, and a mandatory cleaning duty program before school dismissal. The philosophy underlying this approach is the conviction that students with a solid religious understanding will develop into disciplined and responsible individuals, as discipline is viewed as a manifestation of a Muslim's obedience to their faith. These strategies have proven effective in shifting students' perception of discipline from mere school rules to a life value grounded in religion.